CIVIL SOCIETY IN SEARCH OF NEW MEANINGS AND PRACTICES - Шайгордський, Ю.Ж. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Methodological problems and features of the research of the present stage of civil society formationas well as interaction of its institutions and public authorities are reviewed. Attention is focused to finding ways to overcome the crisis of social development and the need to develop its new meanings.